Symptom Severity of Obsessive-Compulsive Disorder Post COVID-19 Pandemic in Psychiatry Department of Tertiary Care Hospital (Journal of Fatima Jinnah Medical University, 2024)
Background: There has been considerable speculation regarding the detrimental effects of the COVID-19 pandemic on mental health. The prevalence of mental disorders is thought to increase during pandemics, and the unique circumstances of the COVID-19 pandemic may have a direct impact on obsessive-compulsive disorder (OCD) manifestation clinically. The objective of the study was to find a mean change in symptom severity of obsessive-compulsive disorder post-COVID-19 pandemic.Patients and methods: A Qausi-experimental study was conducted at the Department of Psychiatry, Jinnah Hospital, Lahore from 05-01-2022 to 05- 07-2022. After approval of the Ethical Review Board and obtaining informed consent, data was obtained from patients focused on available Yale-Brown Obsessive-Compulsive Scale (YBOCS) scores at the start of the COVID-19 pandemic in Pakistan. These patients were re-evaluated using the YBOCS scale to determine any changes in OCD severity, defined as a 50% increase from the baseline (YBOCS) score. All data were recorded on a proforma. All data were recorded on a proforma. Data analysis was performed using IBM SPSS 21. Before and mean change in (YBOCS) was determined by paired sample t-test with a significance level of p≤0.05.Results: The mean age was 36.65±3.892 years. There were 56.7% (n=34) males whereas 43.3% (n=26) were females. Distribution of duration of disease, pre-COVID YBOC score, Post- COVID (YBOCS), and change in (YBOCS) was calculated as 3.52+1.0 years, 18.07+1.9, 28.30+2.149 and 10.33+3.001, respectively.Conclusion: In the current study we found the mean change in symptom severity of obsessive-compulsive disorder post-COVID-19 pandemic using (YBOCS) score. The rise in symptoms and overall severity observed in individuals with OCD may largely stem from the stress induced by the ongoing pandemic.
Keywords: Coronavirus disease; Obsessive Compulsive Disorder; YBOCS